El Sensacionalismo en la Televisión Ecuatoriana :el caso de en Carne Propia - Cisneros Almagro, Belén Nataly (2016)
This research aims to demonstrate that the contents on the program "in the flesh" are sensational, taking into account the analysis of four programs broadcast in prime time from 20:00 to 21:30, by the signal Channel One. Showing how exposed social, addictive and relatives of the protagonists of each story, in urban or marginal areas with high poverty rates in the city of Guayaquil problems. In order to gain rating by sensational information without proper research work. rating tables has obtained the programs analyzed, achieved with statistical data, without explaining high or low is displayed. It is a brief explanation of the meaning and sensationalist way affects the television audience, as the terms of handling and trash TV, to facilitate understanding of research. The contribution of this paper is to society, which will be allowed to know the true reality, which is behind a camera, that will not confuse the need to consume programs for fun or entertainment, also knowing indicating the Organic Law communication, and as viewers have rights of access to information with themes of education and culture.